Measurement of radioactivity and hazard index of Gonadal dose in selected Cement samples in Iraq - Abdulhussein Abdalmear Alkufi; Shatha Farhan Alhous; Shaymaa Awad Kadhim (Journal of the Pakistan Medical Association, 2024)
Given the importance of cement as a basic material in construction, this study was undertaken to evaluate the level of radioactivity in a selected group of cement samples most used in construction to determine whether they are safe for human health. In this investigative study, nine samples of cement, both domestic and imported, that are often used in construction projects in Iraq were gathered. A NaI (Tl) gamma-ray spectrometer (3"x3") was used to measure the radioactivity in the samples. The average specific activity levels in the tested cement samples were 11.373±0.522, 5.795 ± 0.230, and 179.123±2.207 Bq/Kg, respectively. Also calculated was the average of the radium, which was equivalent to 33.449±1.022 Bq/kg. As for the risk indicators, the internal risk coefficient was 0.121±0.004 and external risk coefficient was 0.090 ±0.002. While studying the radiation doses, the values of effective annual internal dose was 0.080 mSv/y, external dose rates were 0.020 mSv/y, absorbed dose ratio was 16.321±0.476 nGy/h, and gamma index was 0.253±0.007. In the end, and depending on what was studied from various variables, with an average of 115.59 Sv/y, the annual gonadal equivalent dose risk (AGED) was calculated. The world average values were used to compare all the results. Finally, it was discovered that the radiation parameter levels of none of the samples had a detrimental effect on human health. Keywords: Radium, Radioactivity, Thallium, Potassium, Uranium, Gamma Rays, Cement